Environmental atitudes of urban dwellers in Kuala Lumpur, Malaysia - Baharuddin, Zainul Mukrim; Othman, Rashidi; Ab Sani, Jasasikin (2017)
Environmental concern on climate change have greater impact to urban health around the globe. Temperature risk, water quality status and air pollution are major threat for living environment including urban biodiversity. Thus, the aim of the paper are to investigate environmental attitude among people in Kuala Lumpur, Malaysia. There are five urban parks around Kuala Lumpur have been selected as case studies and 380 respondents have been participated in the survey questionnaire. Data gathered under the demographic section range of age, gender, ethnicity, levels of education, and income. New Ecological Paradigm (NEP) have been adopted as theory underpinning to identify public concerns. The result have presented that there are significant different among people’s between three ethnicity consist of Malay, Chinese and Indian, six different levels of education and six different income groups. Malays are majorities ethnic and have more attached to nature since childhood and play a vital rules in environmental education. Meanwhile, young generation have greater space in exposure them to importance of protecting earth every in daily routine. Finally, high income level could contribute social, environment and economic benefit opportunities to the societies. Therefore, urban biodiversity policies should focus of these three major elements in promoting environmental concern with in urban dwellers in Kuala Lumpur. Keywords : New Ecological Paradigm, Environmental Attitude, climate change and Urban biodiversity